Penguatan Kreativitas dan Kompetensi Digital Siswa melalui Pelatihan Pembuatan Konten Video Pembelajaran dengan CapCut di SMA Negeri 1 Ungaran - Prasetya, Dany Buyung Yudha; Rohman, Yanuar Lutfi; Setiawati, Ai Sumirah; Nugroho, Yoyok (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The goal of this community service is to optimize the use of digital technology for learning at SMA Negeri 1 Ungaran through project-based differentiated learning. 36 students who are active in school organizations and two teachers who guide student organizations will participate in this service. Through training on the CapCut video editing application, students will develop digital skills and learn to use devices productively for creating video content. CapCut enables students to express their creativity by producing educational content, combining conventional and digital media for differentiated learning. Training results showed a significant increase in students' understanding of positive device usage, with an average post-test score of 78, higher than the pre-test score of 67. Students were enthusiastic during the workshop sessions where they created and edited videos and applied their newfound skills to make useful learning videos. Students also demonstrated the ability to create narratives and communicate through scripts, as well as the ability to search for information on the internet, thus enriching their knowledge on topics of interest. This training benefits both students and teachers by introducing the CapCut application as a tool that can be used in formal learning and extracurricular activities. Thus, the activity successfully contributed to improving students' digital competence and reducing their use of devices for unproductive purposes.